Influência do aumento do comprimento de implantes dentários - Pellizzer, Eduardo Piza [UNESP]; Santiago Júnior, Joel Ferreira [UNESP]; Batista, Victor Eduardo de Souza [UNESP]; Mello, Caroline Cantieri de [UNESP]; Lopes, Leonardo Ferreira de Toledo Piza [UNESP]; Almeida, Daniel Augusto de Faria [UNESP] (My University, 2013)
The use of implants of greater length may be more favorable for the predictability of dental implants. This statement is relevant, since the cause of failures in dental implants are more related to biomechanical complications. The aim of this study was to evaluate the influence of increase of the length around the entire body of the implant. Six models were created with the presence of only one hexagonal implant (Master Screw connection, Implant Systems, São Paulo, Brazil) of 3.75 mm x 7.0 mm (Model A), 3.75 mm x 8.5 mm (Model B ), 3.75 mm x 10.0 mm (Model C) 3.75 mm x 11.5 mm (Model D) 3.75 mm x 13.0 mm (Model E) 3.75 mm x 15.0 mm (Model F) using the method of photoelasticity. The results were visualized through a qualitative analysis of stresses (number and intensity photoelastic fringes). The model A showed a pattern of less favorable stress distribution, the oblique loading was the most detrimental to the related structures. Conclusion: The increased length allowed for a better distribution of stresses. The oblique loading was more detrimental when compared to axial loading.

A utilização dos implantes de maior comprimento pode ser mais favorável para a previsibilidade dos implantes dentários. Essa afirmação é pertinente, uma vez que a causa dos fracassos em implantes osseointegrados está mais relacionada às complicações biomecânicas. Assim, o objetivo deste estudo foi avaliar a influência da ampliação do comprimento ao redor da superfície do implante. Seis modelos foram criados com a presença apenas de um implante (Conexão Master Screw, Sistemas de Próteses, São Paulo, Brasil) do tipo hexágono externo de 3.75 mm x 7.0 mm (Modelo A), 3.75 mm x 8,5 mm (Modelo B), 3.75 mm x 10.0 mm (Modelo C), 3.75 mm x 11.5 mm (Modelo D), 3.75 mm x 13 mm (Modelo E), 3.75 mm x 15 mm (Modelo F) utilizando a metodologia de fotoelasticidade. Os resultados foram visualizados através de uma análise qualitativa de tensões (número e intensidade de franjas). O modelo A apresentou um padrão de distribuição de tensões menos favorável; o carregamento oblíquo foi o mais prejudicial para as estruturas relacionadas. Conclusão: O aumento do comprimento permitiu uma melhor distribuição de tensões. O carregamento oblíquo foi o mais prejudicial, quando comparado com o carregamento axial.
Influence of increasing the length in dental implants
Keywords: Dental Implants; Dental prosthesis; Biomechanics; Implantes dentários; Prótese dentária; Biomecânica